An assessment of current practices and needs analysis of users in university industry linkages: a study in UiTM / Raenah Md Sem, Noraini Ismail and Dang Merduwati Hashim - Md Sem, Raenah; Ismail, Noraini; Hashim, Dang Merduwati (2005)
UiTM has set up a centre called the UiTM lndustry Linkages Centre or UILC in mid-2003. The main role and function is to enable the university to provide a platform for a concerted and coordinated effort in addressing the various demands and needs of such linkages on the diverse requirements of the industry and various faculties of the university. The Center needs to conduct a pilot study to evaluate the extent of linkages so far attained by the members of the different units or faculties, the curriculum so far implemented or the extent of the teaching staff's attachment to industry, among others. As such this study aims to assess: (i) to assess the extent of current practices and (ii) the status of university industry linkages of UiTM lecturers and how they would view the role of the Centre. The first stage of the research was to conduct a focus group dialogue followed by the development of the research instrument and the field survey. A focus group dialogue was conducted with 6 companies representing the various sectors on 25 February 2004 at UiTM Hotel.